Tendances et prospectives d’avenir de l’économie-monde - Wallerstein, Immanuel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
One of the aspects characterizing the state of International Relations at the moment is the increasing emphasis on political economy. This is the approach of the present paper. It is more in the form of succinct propositions than detailed analysis, since the latter is available in the author' s previous writings. Specifically, the paper concentrates on five aspects: the nature of the world economy, its mode of functioning, its basic tendencies, the crisis of the global system, and future prospects of evolution the paper emphasizes both the interconnectedness of the different levels of analysis (from the family to the world system) as well as the importance of a diachronic and macro-structural approach.